Bronze Age Eleusis and the origins of the Eleusinian Mysteries - Kosmopulos, Michaēl B. (Cambridge University Press, 2015)
This book provides a synthesis of the archaeology of Eleusis during the Bronze Age, reconstructing the origins and early development of the Eleusinian Mysteries